LIDERAZGO FEMENINO EMPRESARIAL Y EL COMPROMISO ORGANIZACIONAL EN EL SECTOR DE CONFECCIÓN TEXTIL - Pardo-Paredes, Eleonor Virginia (2018)
With the desire to contribute to the textile manufacturing sector, important in the industrial production of the region, we study the profile of female business leadership and organizational commitment. This approach aims to answer the question: How does female entrepreneurial leadership influence the organizational commitment of the garment sector? The present study aims to positively impact on the management of the concept of social and gender equity, a bet that also coincides with the National Development Goals and the Sustainable Development Goals. With a qualitativequantitative methodology (phenomenological study of empirical phenomenological approach, descriptive-correlational scope, cross-section, non-experimental design), quantitative instruments were used: situational leadership test (Hersey & Blanchard, 1974), leadership perception test (Mellado-Ruiz, 2005), organizational commitment test (Meyer & Allen, 1997) and qualitative instruments: Interview guide on female business leadership (Bucarey & López, 2016; Contreras, Pedraza & Mejía, 2012; Batista & Bermúdez, 2009 and Gómez, 2006) and the interview guide on organizational commitment (Claure-Rocha & Böhrt-Pelaez, 2004 and Bayona, Goñi-Legaz & Mandorrán, 1999) duly validated. The processing of the data was with SPSS (quantitative) and Atlas.ti (qualitative). The research has been validated by specialists in the area of human talent management and social and gender equity, through a checklist. The selection of specialists was by Delphi. The research was carried out in a population of eleven businesswomen and their 46 collaborators of the Textile Confederation Association of Tungurahua (ACONTEX), determined with a nonprobabilistic sampling intention.